2013
DOI: 10.1371/journal.pone.0053058
|View full text |Cite
|
Sign up to set email alerts
|

“How Can I Gain Skills if I Don’t Practice?” The Dynamics of Prohibitive Silence against Pre-Marital Pregnancy and Sex in Zimbabwe

Abstract: Young people face sexual and reproductive health (SRH) problems including Human immunodeficiency virus (HIV) and Acquired immunodeficiency syndrome (AIDS). It is critical to continue documenting their situation including the contexts they live in. As part of a larger study that explored perspectives of men to SRH and more specifically abortion and contraceptive use, 546 pupils (51% female; age range 9–25 years) from a rural area in Zimbabwe were invited to write anonymously questions about growing up or other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
(37 reference statements)
2
10
0
1
Order By: Relevance
“…Our findings are also similar to SRH results reported elsewhere in sub-Saharan Africa. A study in Zimbabwe found that adolescents feared pregnancy and its potential social, financial, educational and health impact [ 28 ]. A systematic review conducted to explore the limits of modern contraceptive use found that lack of knowledge hindered use [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also similar to SRH results reported elsewhere in sub-Saharan Africa. A study in Zimbabwe found that adolescents feared pregnancy and its potential social, financial, educational and health impact [ 28 ]. A systematic review conducted to explore the limits of modern contraceptive use found that lack of knowledge hindered use [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the perceived consequences of not obeying taboos and as such the general people will leave the culprit to deal with his/her problems because they did not obey the values of the society. Silence on HIV issues may also mean lack of understanding, fear, shame or lack of confidence to talk about such issues (Chikovore, et al, 2013). The unwillingness of people and particularly organisations to talk about HIV/AIDS may signal the need to have HIV specialists in organisations to deal with such issues.…”
Section: Hiv and Aids A Taboo Subjectmentioning
confidence: 99%
“…Research suggests that there is strong parental denial of adolescent sexuality in Zimbabwe and challenges in tackling SRHR within families (Chikovore et al, 2013;Chiweshe and Chiweshe, 2017).…”
Section: Ta B L E 1 Age Of Respondentsmentioning
confidence: 99%
“…High adolescent pregnancy rates compound economic burdens and perpetuate trajectories of poverty as adolescent mothers are inclined to have poor structural resources available to them (Nash et al, 2019). In Zimbabwe, the adolescent pregnancy rate is 21% for age 15-19 and adolescent fertility 120 per 1,000 girls and 70 per 1,000 girls for rural and urban areas, respectively (Chikovore et al, 2013).…”
Section: Introductionmentioning
confidence: 99%